EFFECT OF ADDING GARLIC ALLIUM SATIVUM POWDER IN DIET ON HEMATOLOGICAL, BIOCHEMICAL AND HISTOPATHOLOGICAL CRITERIA OF COMMON CARP CYPRINUS CARPIO L. - Mahmoud Ahmad Mohammad (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2023)
Common carp was fed at a rate of 9 ± 0.4 g/fish for a period of 56 days on four experimental diets with three replications per diet, including the addition of garlic powder to a diet containing 0 % (control diet,T1), while T2,T3 and T4 at 1.00, 1.50 and 1.75 %, respectively. Fish fed on experimental garlic-containing diet show a significantly changes (P≤ 0.05) in Packed Cell Volume and Hemoglobin as compared with the control diet. There were no significant differences in MCHC and neutrophil counted, while the albumin value of fish fed on the 2nd diet increased significantly (P≤ 0.05) among all treatments. The values of ALT (except for diet 2) and AST decreased significantly (P≤ 0.05) compared with control diet. Results of histological examination of intestine for fish fed on garlic at 1.00% showed presence of edema at the top of the villi, while the lesion was more severe in intestine of fish fed on garlic at 1.5 and 1.75%., Likewise, histological examination of the liver of carp fed garlic at 1.00, 1.5 and 1.75% showed histopathological alteration - represented by pyknosis and vacuolar degeneration of hepatocyte with atrophy of pancreas and hemorrhage. It is evident from the above that the addition of garlic powder has led to an improvement in blood and biochemical characteristics, but the addition of garlic has had some negative effects on the histological characteristics of the intestine and liver, possibly as a result of the long-term feeding of fish to these proportions of garlic.